Identification of Biomarker-Based Strategies for Managing Chronic Inflammation in Polycystic Ovarian Syndrome to Alleviate Population-Level Disease Burden - Shamim Akram, Salma Kadir, Maham Khalid, Marifat Shah, Sajida Imran, Aaisha Qadir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic Ovarian Syndrome (PCOS) is a common endocrine disorder of women of reproductive age with chronic inflammation, insulin resistance, and metabolic dysfunction. Although it is common in Pakistan, PCOS is underdiagnosed and contributes to the development of infertility, cardiovascular disease, and metabolic complications. As a result, the identification of biomarkers for early diagnosis and effective management of the disease requires strategies based on chronic inflammation. Objectives: This study was designed to evaluate inflammatory biomarkers in PCOS patients to compare them with healthy controls and to evaluate the relationship with the metabolic parameters to establish potential diagnostic and therapeutic targets of PCOS. Methods: A cross-sectional study was done at tertiary care hospitals in Lahore, Pakistan, among 120 PCOS patients and 60 age-matched healthy controls. Enzyme-linked immunosorbent assay (ELISA) was used to determine serum levels of C reactive protein (CRP), interleukin 6 (IL 6), and tumor necrosis factor-alpha (TNF alpha). Anthropometric and metabolic parameters, which included BMI, WHR, FBG, HOMA-IR, and lipid profile, were assessed. SPSS 25.0 was used to perform statistical analysis, and p < 0.05 was taken as statistically significant. Results: The CRP, IL-6, and TNF-α levels were significantly elevated in PCOS patients compared to controls (p < 0.001). Chronic inflammation is also related to metabolic dysfunction as BMI, WHR, insulin resistance, and dyslipidemia are significantly higher. Conclusion: PCOS is characterized by a pro-inflammatory state, which, together with metabolic and cardiovascular risks, contributes to the pathogenesis of PCOS. This could enable early detection and personalized treatment strategies via biomarker-based screening. Future research will be directed towards Anti-inflammatory interventions, Genetic markers, and Targeted therapies to enhance the management of PCOS in Pakistan. Keywords: PCOS, Chronic Inflammation, Biomarkers, CRP, IL-6, TNF-α, Insulin Resistance, Metabolic Syndrome, Pakistan.